The meaning of open-water swimming for adults in Ireland: a qualitative study. Issue 2 (4th November 2021) - Murray, Edel; Fox, Jackie
Abstract : Purpose: There has been an increase in swimming in natural bodies of water as reported in personal qualitative accounts. However, limited academic research has explored the meaning of this occupation. Engaging with nature, exercising and being part of a community contribute to better mental and physical health. The purpose of this research was to explore the meaning that adults attribute to open-water swimming in natural bodies of water. Design/methodology/approach: This study used phenomenological interviews to explore the meaning that five adults attribute to open-water swimming. Findings: Open-water swimming contributes to meaning-making in many ways. Participants reported swimming as necessary for maintaining mental and emotional well-being and forming meaningful connections with the social environment, nature and their true selves. Research limitations/implications: This study contributes to the understanding of the meaning of open-water swimming for adults in Ireland. Understanding the meaning of this occupation may add to the body of evidence exploring blue-space to promote health. Originality/value: Open-water swimming is an occupation growing in popularity. This is the first paper to explore open-water swimming from an occupational perspective. This may provide an alternative perspective for viewing blue-space engagement and understanding the relationship between health, blue-space occupations and our oceans.